Guía clínica de enfermedad pulmonar obstructiva crónica (EPOC). Parte I: diagnóstico - Ruiz C., Mauricio (Revista Hospital Clínico Universidad de Chile, 2008)
Chronic obstructive pulmonary disease (COPD) is characterized by the presence of chronic obstructive and poorly reversible airway obstruction secondary to an abnormal inflammatory reaction mainly against the smoke snuff. This is an entity that is often underdiagnosed and that his diagnosis and staging requires the realization of a spirometry which should show varying degrees of obstruction to expiratory flow. In the clinical assessment is important to establish the magnitude of smoking, as well as the intensity of the designs and its progression. If the smoking does not disclose the bronchial obstruction must questioning about other pollutants,especially intradomiciliary with exposure to wood smoke. This first part of the guide discusses the clinical diagnostic criteria assessing the severity and criteria for referral of COPD.